Speaking of—and as—Stigma: Performativity and Parkinson's in the Rhetoric of Michael J. Fox - Nicole Quackenbush (Disability Studies Quarterly, 2011)
In this essay, I utilize the intersections between disability theory and rhetorical theory to identify two key and interconnected stages of actor and activist Michael J. Fox's performativity of disabled identity: first, a rhetoric of passing and second, a rhetoric of masquerade. Ultimately, I claim that Fox as a visibly disabled rhetor speaks both as stigma—because his rhetoric issues from and through his body as he experiences Parkinso'’s disease—and of stigma—because he performs disability not just to provide an exigency for research into cures but also to challenge the cultural norms that dehumanize the disabled subject.
Keywords: Masquerade; Parkinson' s; passing; performativity; rhetoric; stigma